FDR's body politics : the rhetoric of disability - Houck, Davis W. (Texas A & M University Press, 2003)
Franklin Roosevelt instinctively understood that a politician of his era who was unable to control his own body would be perceived as unable to control the body politic. He therefore took great care to hide his polioinduced lameness both visually and verbally. In FDR's Body Politics, Davis W. Houck and Amos Kiewe draw on never-before-used primary sources to analyze the silences surrounding Roosevelt's disability, the words he chose to portray himself and his policies as powerful and health-giving, and the methods he used to maximize the appearance of physical strength. They examine his broad strategies, as well as the speeches Roosevelt delivered during his political comeback after polio struck, to understand how he overcame the whispering campaign against him in 1928 and 1932. Ultimately, this is a story of triumph and courage that reveals a master politician's understanding of the body politic in the most fundamental of ways.
Keywords: Roosevelt, Franklin D. -- (Franklin Delano), -- 1882-1945 -- Health.; Roosevelt, Franklin D. -- (Franklin Delano), -- 1882-1945 -- Language.; Roosevelt, Franklin D. -- (Franklin Delano), -- 1882-1945 -- Public opinion.; Roosevelt, Franklin D -- (Franklin Delano), -- 1882-1945; Roosevelt, Franklin D. -- (Franklin Delano), -- 1882-1945 -- Santé; Roosevelt, Franklin D. -- (Franklin Delano), -- 1882-1945 -- Langage.; Roosevelt, Franklin D. -- (Franklin Delano), -- 1882-1945 -- Opinion publique.; Roosevelt, Franklin D. -- (Franklin Delano), -- 1882-1945; Physical fitness -- Political aspects -- United States -- History -- 20th century.; Rhetoric -- Political aspects -- United States -- History -- 20th century.; Human body -- Social aspects -- United States -- History -- 20th century.; People with disabilities -- United States -- Biography.; Presidents -- United States -- Biography.; United States -- Politics and government -- 1933-1945.; English language -- United States -- Rhetoric.; Public opinion -- United States.; Health attitudes.; Politics, Practical.; Misinformation.; Persons with Disabilities -- psychology.; Attitude to Health; Communication; History, 20th Century; Human Body; Politics; United States; Condition physique -- Aspect politique -- États-Unis -- Histoire -- 20e siècle.; Discours politique -- États-Unis -- Histoire -- 20e siècle.; Corps humain -- Aspect social -- États-Unis -- Histoire -- 20e siècle.; Personnes handicapées -- États-Unis -- Biographies.; Présidents -- États-Unis -- Biographies.; Anglais (Langue) -- États-Unis -- Rhétorique.; Opinion publique -- États-Unis.; États-Unis -- Politique et gouvernement -- 1933-1945.; Attitudes à l'égard de la santé.; Médecine -- Histoire -- 20e siècle.; Politique.; Mésinformation.; politics.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; HISTORY.; Politics, Practical; Health attitudes; English language -- Rhetoric; Health; Human body -- Social aspects; Language and languages; People with disabilities; Politics and government; Presidents; Public opinion; Rhetoric -- Political aspects; 1900 - 1999; Biography; collective biographies.; Biographies; History; Biographies.